Acute Myeloid Leukemia in a Three-Year-Old Girl Mimicking Chronic Myeloid Leukemia in Blast Crisis, Challenge in Diagnosis and Treatment in Limited-Resourced Health Care Facility: A Case Report - Predani, Ni Luh Putu Diaswari; Gunawan, Andre; Mustika, Putu Pradnyanita; Tedja, I Gusti Ayu Wiradari (http://dharmais.co.id/, 2024)
Introduction: : Acute myeloid leukemia (AML) is the second most common hematologic cancer in childhood. Clinically, AML has similar symptoms to other types of leukemias, and diagnosis remains a challenge due to limited access to pediatric hemato-oncology diagnostic examination. This study aims to report AML in a 3-year-old girl who was first suspected of Chronic Myeloid Leukemia (CML) in blast crisis, using a combination of clinical-hematology parameters and conventional morphology examination in a limited-resourced healthcare facility. Case Presentation: A 3-year-old girl was referred from a rural Eastern Indonesia hospital with symptoms of prolonged fever, leucocytosis, severe anemia, and severe thrombocytopenia. In the previous hospital, the patient had a history of hyperleukocytosis and peripheral blood smear suspected of CML in blast crisis. A peripheral blood smear was repeated in our hospital and showed findings of Auer rod cells suggesting AML. Two bags of packed red cells and 2 thrombocyte concentrations were administered before referral for further diagnostic evaluation with bone marrow aspiration. Bone marrow aspiration revealed multiple nucleoli suggested for AML with FAB classification as M4 subtypes, and she received chemotherapy in a tertiary hospitalConclusions: With limited resources, suspicion based on persistent clinical symptoms, routine hematology tests, and peripheral blood smear examination are important to distinguish AML from CML in blast crisis. Understanding clinical hematology parameters and peripheral blood smears is the first step in AML diagnosis pathway and decision for further diagnostic referral. Supportive therapy and early recognition of oncologic emergency must be done before referral to a tertiary referral hospital.